The effectiveness of Chair Massage on Stress and Pain in Oncology - Borges de Souza, PhD, Talita Pavarini; Fumiko Sato Kurebayashi, PhD, Leonice; Nery de Souza-Talarico, PhD, Juliana; Natalia Teresa Turrini, PhD, Ruth (International Journal of Therapeutic Massage & Bodywork, 2021)
Background: There is a high prevalence of moderate-to-high levels of chronic stress among nurses, as well as an occurrence of musculoskeletal disorders. Purpose: To evaluate the effectiveness of chair massage to reduce chronic stress and musculoskeletal pain in the Oncology Nursing team. Setting: Two teaching cancer hospitals, one public and the other private, in São Paulo city, Brazil. Participants: A total of 60 women from the Oncology Nursing team. Research Design: A randomized controlled trial divided into two groups: chair massage and control without intervention. Intervention: The massage group received two chair massage sessions lasting 15 minutes, twice a week, for three weeks. Main Outcome Measure: Reduction of stress and pain measured by the List of Signs and Symptoms (LSS) and the Brief Pain Inventory (BPI), respectively. Results: The average age was 32 (± 5.3) years. There was a reduction of stress measured by the LSS with a statistical difference in the group-time interaction (p < .001), with a Cohen’s d value of 1.21 between groups. The BPI analysis showed a statistically significant difference in the group-time interaction for general activity (p < .008), mood (p < .03), work (p < .000), and sleep (p = .03), with reduced pain interference in these components. Conclusion: Chair massage reduced stress and pain interference in the team’s daily life activities, bringing a positive impact in the context of work stress and pain in Oncology nursing professionals.